2020
DOI: 10.29103/j-mind.v4i1.3372
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Budaya Organisasi Dan Gaya Kepemimpinan Terhadap Kinerja Guru Dengan Lingkungan Kerja Dan Kepuasan Kerja Sebagai Varibel Intervening Pada Guru Sma Di Kecamatan Dewantraa Kabupaten Aceh Utara

Abstract: This study aims to determine the effect of organizational culture and leadership style on teacher performance with work environment and job satisfaction as an intervening variable. The data used are primary data by distributing questionnaires to 140 respondents, namely teachers who teach at Senior High Schools in Dewantara District, North Aceh Regency. The method used to analyze the data is Structural Equation Modeling (SEM). The results of the study found that the organizational culture and work environment h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
3
1
0
Order By: Relevance
“…These results prove that the higher the organizational culture, the more it improves teacher performance in real terms It can be interpreted that there is a positive influence of organizational culture on improving teacher performance in MTs Negeri 8 Sragen. Furthermore, this is in line with previous research conducted by (Nurlaili, Apridar et al, 2019) explaining that organizational culture has a positive and significant effect on the work environment and teacher performance, in addition to the above opinions, this is also in line with the research conducted by (Muntasir & A.samad, 2021) explained: (1) The organizational culture that has been run in the Samalanga Kabupaen Bireuen District State High School school, according to the perception of teachers has been going well in supporting teacher performance. (2) Verifiative research results based on causality analysis between variables prove; a) there is a significant influence of organizational culture on teacher performance.…”
Section: B the Influence Of Organizational Culture On Teacher Perform...supporting
confidence: 90%
See 1 more Smart Citation
“…These results prove that the higher the organizational culture, the more it improves teacher performance in real terms It can be interpreted that there is a positive influence of organizational culture on improving teacher performance in MTs Negeri 8 Sragen. Furthermore, this is in line with previous research conducted by (Nurlaili, Apridar et al, 2019) explaining that organizational culture has a positive and significant effect on the work environment and teacher performance, in addition to the above opinions, this is also in line with the research conducted by (Muntasir & A.samad, 2021) explained: (1) The organizational culture that has been run in the Samalanga Kabupaen Bireuen District State High School school, according to the perception of teachers has been going well in supporting teacher performance. (2) Verifiative research results based on causality analysis between variables prove; a) there is a significant influence of organizational culture on teacher performance.…”
Section: B the Influence Of Organizational Culture On Teacher Perform...supporting
confidence: 90%
“…Another factor that affects teacher performance is organizational culture. According to (Nurlaili, Apridar et al, 2019) explain that organizational culture has a positive and significant influence on the work environment and teacher performance, in addition to the above opinions, this is in line with the research conducted by (Muntasir & A.samad, 2021) explaining the results of verifiative research based on causality analysis between proven variables; a) there is a significant influence of organizational culture on teacher performance, research conducted (Meri., 2020) explains There is a significant influence of organizational culture on teacher performance, other research (Fitria, 2018) explains that there is a direct influence of organizational culture on teacher performance. Based on several opinions concluded that organizational culture has a positive and significant effect on teacher performance, this shows that organizational culture is one factor that determines teacher performance.…”
Section: Introductionsupporting
confidence: 70%
“…These results were confirmed based on research results from (Nurlaili et al, 2020) which revealed that the work environment fully mediates the influence of leadership style on organizational performance. In addition, research from (Ichsan et al, 2021) explains that the factor that makes employee performance better is by embedding a good work environment, so that organizational leaders apply their leadership style according to the expectations of each employee.…”
Section: Work Environment As a Mediation Between Leadership Styles An...supporting
confidence: 64%
“…Human resource management is a process consisting of planning, organizing, leading and controlling activities related to job analysis, job evaluation, procurement, development, compensation, promotion, and termination of employment in order to achieve the stated goals (Nurlaili, et, al., 2020).…”
Section: Human Resource Managementmentioning
confidence: 99%